First Study on Chromosomal Feature and NORs Localization of the Yellow-spotted Keelback Snake, Fowlea flavipunctatus (Squamata, Natricinae) in Thailand - Nattasuda Donbundit; Weera Thongnetr; Isara Patawang; Alongklod Tanomtong (Science Technology and Engineering Journal (STEJ), 2020)
The first report on chromosome of the yellow-spotted keelback snake (Fowlea flavipunctatus), from Khon Kaen Province, Thailand, was investigated using classical cytogenetic approach. The mitotic chromosomes were directly prepared from the bone marrow cells of four adult male and female specimens after in vivo colchicine treatment. The results shown that the diploid chromosome number was 2n=42, while the fundamental number (NF) was 58 in both male and female. The types of macrochromosome were six large metacentric (m), two large acrocentric (a), four small metacentric and four small telocentric (t) chromosomes, and 24 microchromosomes (mim 2 + mit 22). Nucleolar organizer regions (NORs) located on subtelomeric position of short arm of macrochromosomes pair 4. The sex chromosome system was ZW. The karyotype formula of F. flavipunctatus is as follows: 2n (42) = Lm 6 + La 2 + Sm 4 + St 4 + mim 2 + mit 22 + 2 sex chromosomes (ZW).